2014
DOI: 10.1128/aem.02092-14
|View full text |Cite
|
Sign up to set email alerts
|

Application of Long-Range and Binding Reverse Transcription-Quantitative PCR To Indicate the Viral Integrities of Noroviruses

Abstract: This study intends to establish and apply methods evaluating both viral capsid and genome integrities of human noroviruses (NoVs), which thus far remain nonculturable. Murine norovirus 1 (MNV-1) and human NoV GII.4 in phosphate-buffered saline suspensions were treated with heat, UV light, or ethanol and detected by reverse transcription-quantitative PCR (RT-qPCR), long-range RT-qPCR, binding RT-qPCR, and binding long-range RT-qPCR. For MNV-1 heated at 60°C for 2 and 30 min, limited reductions of genomic copies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 35 publications
4
28
0
Order By: Relevance
“…It is generally recognized that surrogates and hNoV survive in a variety of raw, processed, and/or stored foods, including berries, herbs, and molluscan shellfish (Baert et al, 2009;Verhaelen et al, 2012;Richards, 2012;Richards et al, 2012;Poschetto et al, 2007;Butot et al, 2008;Li et al, 2014;Sánchez et al, 2011;Lou et al, 2012). Studies have also shown that the food matrix and environmental factors have a significant impact on virus survival (Le Guyader and Atmar, 2008;Sobsey and Meschke, 2003).…”
Section: Citationmentioning
confidence: 97%
“…It is generally recognized that surrogates and hNoV survive in a variety of raw, processed, and/or stored foods, including berries, herbs, and molluscan shellfish (Baert et al, 2009;Verhaelen et al, 2012;Richards, 2012;Richards et al, 2012;Poschetto et al, 2007;Butot et al, 2008;Li et al, 2014;Sánchez et al, 2011;Lou et al, 2012). Studies have also shown that the food matrix and environmental factors have a significant impact on virus survival (Le Guyader and Atmar, 2008;Sobsey and Meschke, 2003).…”
Section: Citationmentioning
confidence: 97%
“…Using a combination of RNase pretreatment and binding to cultured mammalian cells (Caco-2), with the hypothesis that only undamaged virus particles will bind to the cells, Li et al (45) observed a~1.5log reduction in detectable NoV GII.4 GE at 708C for 2 min and a 2.3-log reduction at 858C for 2 min. Li et al (47) extended their study using a combination of binding to Caco-2 cells with subsequent long-range RT-qPCR. Following heat treatment at 608C for both 2 and 30 min, they observed~3-log reductions in detectable NoV GII.4 GE.…”
Section: Ethanolmentioning
confidence: 99%
“…Dancho et al (16), using the PGM-MB binding assay, observed that treatment with 0.5 JÁcm À2 caused a 1.8-log reduction in NoV GI detectable by RT-PCR, whereas after a treatment with 2 JÁcm À2 , a 3.8-log reduction in binding was observed. Li et al (47) used a combination of binding to Caco-2 cells with subsequent long-range RT-qPCR. Following exposure of NoV GII.4 to 20 mJÁcm À2 and 200 mJÁcm À2 ,~3 log-and .4-log reductions in detectable GE were observed, respectively.…”
Section: Hhpmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, RT-PCR and quantitative RT-PCR (RT-qPCR) have been widely used for the detection of HuNoVs (Kageyama et al, 2003; Trujillo et al, 2006; Yu et al, 2015). However, these molecular approaches have limited value in distinguishing infectious viruses from non-infectious viruses or free viral RNA (Li et al, 2014; Wang and Tian, 2014). …”
Section: Introductionmentioning
confidence: 99%